966 The Surgical Handbook: Enhancing Surgical Education for Medical Students and Foundation Doctors. (19th August 2022) - Vincent, E; Thenabadu, S; Yiu, C; Ayeni, A; Osa-Iduma, A; Mishra, V
Abstract: Aim: In recent years, the GKT School of Medical Education has introduced a new curriculum resulting in a shift from a single surgical block to an integrated approach. After recognising the potential challenges that the lack of standardisation across various hospitals may cause, we created the Surgical Handbook to supplement learning, improve confidence in approaching surgical patients and prepare students for the United Kingdom Foundation Programme (UKFP). Method: We sought authorisation for the Surgical Handbook from the GKT medical education faculty, assembled a team and conducted further background research. The National Undergraduate Curriculum by the Royal College of Surgeons of England was an excellent resource in the design of the Surgical Handbook . The handbook underwent multiple cycles of review by senior medical education faculty before its final digital and physical distribution for students. Results: The Surgical Handbook has resulted in a sustained positive impact on surgical education for GKT students, with feedback highlighting it as an excellent additional resource for placements, exams, and the Foundation Programme. Conclusions: Most doctors in the United Kingdom will undertake a surgical rotation as part of the Foundation Programme. Preparation for this role is essential and linked to the quality of undergraduate surgical education. Nevertheless, the importance of surgical teaching within the undergraduate curriculum remains a topic of debate. Our Surgical Handbook addresses this issue, and we are in the process of collaborating with other medical schools across the United Kingdom and beyond.